2022
DOI: 10.3390/ijerph192214625
|View full text |Cite
|
Sign up to set email alerts
|

Walking Behavior of Older Adults in Temuco, Chile: The Contribution of the Built Environment and Socio-Demographic Factors

Abstract: The amount of walking for daily transport has decreased significantly over the last decades in Temuco, Chile. Moreover, the percentage of older adults (aged over 65) who did not meet the recommendations of at least 150 min of physical activity per week has increased during this time. In this regard, the present study examines the contribution of socio-demographic and built environment factors on the walking behavior of older adults in Temuco, Chile, with a view to improving their level of physical activity. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Previous studies on the neighborhood scale have demonstrated the relationship between walking for recreation and environmental factors, including land use mix [25]; the presence of walking trails [26]; infrastructure for walking, including the state of the footpath and the standard of its surface [27,28]; the proximity of recreational facilities [26,28]; the presence of accessible destinations (mostly services) like shops, parks, and beaches [27,29]; the availability of public transit services, including factors like proximity to bus stops and public transportation [29,30]; nearby non-residential locations [31]; and perceived and actual traffic safety, including elements like the percentage of street length with speed limits [26,29]; personal security, including less concern about crime [27,32]; and perceived neighborhood aesthetics, as well as the existence of aesthetic elements like the proportion of tree canopy coverage, the upkeep of walkways, cleanliness, and the view of the architecture [26,27,33]. In addition, Borst et al [15] evaluated the relationships between the perceived attractiveness of streets for walking and (physical) street characteristics.…”
Section: Walking For Recreation and Its Associated Built Environmenta...mentioning
confidence: 99%
“…Previous studies on the neighborhood scale have demonstrated the relationship between walking for recreation and environmental factors, including land use mix [25]; the presence of walking trails [26]; infrastructure for walking, including the state of the footpath and the standard of its surface [27,28]; the proximity of recreational facilities [26,28]; the presence of accessible destinations (mostly services) like shops, parks, and beaches [27,29]; the availability of public transit services, including factors like proximity to bus stops and public transportation [29,30]; nearby non-residential locations [31]; and perceived and actual traffic safety, including elements like the percentage of street length with speed limits [26,29]; personal security, including less concern about crime [27,32]; and perceived neighborhood aesthetics, as well as the existence of aesthetic elements like the proportion of tree canopy coverage, the upkeep of walkways, cleanliness, and the view of the architecture [26,27,33]. In addition, Borst et al [15] evaluated the relationships between the perceived attractiveness of streets for walking and (physical) street characteristics.…”
Section: Walking For Recreation and Its Associated Built Environmenta...mentioning
confidence: 99%
“…In particular, in this paper, we focus on the contribution that accessing a street market by foot may provide to food security. Food security can be defined as "access by all people at all times to enough food for an active, healthy life" [28]. The concept also refers to the possibility to physically access food and has been investigated in relation with older people as a significant issue for their well-being [40][41][42].…”
Section: Ferias Libres and Food Security In An Unequal Countrymentioning
confidence: 99%
“…Drawing on these elements, this paper assesses walking access to street markets, considering their key role as a contributor to an urban population's urban well-being and especially to one of its fragile groups, such as older people. Our research has a geographical focus on Chile, a country where the population is rapidly ageing and elderly issues are gaining more attention, as well as in relation to urban mobility and the issues of urban justice that it raises [27][28][29][30][31]; despite this, public policies for ageing are only starting to be implemented [32]. Moreover, like many other Latin America countries, this is an ageing country with an unequal pension system, which makes it relevant for older people to access healthy and inexpensive food.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on a neighborhood scale has discovered a relationship between walking for recreation and environmental factors, including land use mix [15], the availability of paths for walking [16], infrastructure for walking, including its condition and quality of the surface [17,18], the proximity of recreational facilities [16,18], the presence of accessible destinations such as stores, parks, and beaches [17,19], the presence of public transportation facilities [19,20], surrounding non-residential areas [21], perceived and actual traffic safety, including elements like the proportion of a street's length that has speed limits [16,19], less worry about crime and increased personal security [17,22], and the person's perception of the aesthetics of their area, as well as the presence of aesthetic elements such the amount of tree canopy covering, the upkeep of walkways, cleanliness, and the view of architecture [16,17,23]. Additionally, Borst et al [14] examined the connections between the perceived attractiveness of streets for walking and (physical) street characteristics.…”
Section: Literature Review 21 Walking For Recreation and The Built En...mentioning
confidence: 99%